Differentially Expressed Genes in Marine Medaka Fish (Oryzias javanicus) Exposed to Cadmium - Woo, Seonock; Son, Sung Hee; Park, Hong-Seog; Vulpe, Chris D.; Ryu, Jae-Chun; Yum, Seungshic (KOREAN SOCIETY TOXICOGENOMICS & TOXICOPROTEOMICS-KSTT, 2008)
To screen the differentially expressed genes in cadmuim-exposed marine medaka fish (Oryzias javanicus), a candidate marine test fish for ecological toxicity, the differential display polymerase chain reaction (DD-PCR) was carried out, since the genome-wide gene expression data are not available in this fish species yet. A total of 35 clones were isolated from cadmium-exposed fish and their nucleotide sequences were analyzed. The differentially expressed gene candidates were categorized to response to stimulus (3); ion binding (3); DNA binding (1); protein binding (6); carbohydrate binding (1); metabolic process (4); biological regulation (3); cellular process (2); protein synthesis (2); catalytic activity (2); sense of sight (1); immune (1); neurohormone (1); signaling activity (1); electron carrier activity (1) and others (3). For real-time quantitative RT-PCR, we selected catalase, glucose-6-phosphate dehydrogenase, heat shock protein 70, and metallothionein and confirmed that cadmium exposure enhanced induction of these four genes.
Keywords: TROUT SALMO-TRUTTA; OXIDATIVE STRESS; JAVA-MEDAKA; ANTIOXIDANT ENZYMES; MESSENGER-RNA; INDUCTION; METALLOTHIONEIN; BIOMARKERS; DISPLAY; CELLS